KEKERASAN SEKSUALITAS TERHADAP PEREMPUAN OLEH SUAMI DITINJAU DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG KEKERASAN DALAM RUMAH TANGGA (KDRT) - Anak Agung Putu Wiwik Sugiantari; Lis Julianti; Gusti Bagus Ngurah Agung (Jurnal Hukum Saraswati (JHS), 2019)
The existence of the Law on violence in the household indeed seems to give new hope to the resolution of some women's issues. Besides because this law contains various rules governing the prevention, protection and restoration of victims of domestic violence, it also regulates specifically the violence that occurs in households, such as physical, psychological, economic and sexual violence with elements of criminal acts especially different with criminal acts of persecution like those in the Criminal Code. In addition, this law also regulates the obligations of law enforcement officers, health workers, social workers, escort volunteers or spiritual guides to protect victims of violence so that they are more sensitive and responsive to the interests of creating integrity and harmony as expected. The problem is that if we look closely, we will find a variety of legal loopholes which, instead of allowing this law to provide solutions to community problems, may actually create new problems, even legitimize moral deviations in society. . This is related to the weakness of the underlying thinking paradigm / perspective along with assumptions and definitions used in developing legal material. Just as the article on the prohibition of sexuality violence regulated in this Law has multiple interpretations, so that when compared to Islamic law there are several contradictions in the article, so that a solution is needed.